Fire Strike: Oregon Files # 17 - Maden, Mike; Cussler, Clive (New York : G. P. Putnam's Sons, 2023)
"When Cabrillo is hired to extract an undercover operative in Kenya, he finds himself on the trail of a deadly international plot. A Saudi Prince seeks to unleash a deadly assault on U.S. forces, sparking a new war in the Middle East and ultimately destroying Israel. Cabrillo's crew have met their most fearsome adversaries yet: a force of bio-hacked soldiers endowed with extreme strength and stamina and an unquenchable appetite for violence. The Oregon team must journey from the Amazon rainforest to an abandoned monastery in Eritrea before a final showdown in the mountains of Yemen, using every shred of courage and cunning they can muster to disable the ship-killer missile before the Arabian Sea becomes a mass grave"--.
new book 2023 summer.
Keywords: Suspense fiction; Intelligence service; Ship captains; Novels; Thriller fiction